Intranasal administration of allergen increases specific IgE whereas intranasal omalizumab does not increase serum IgE levels—A pilot study. Issue 5 (12th December 2017) - Eckl‐Dorna, J.; Fröschl, R.; Lupinek, C.; Kiss, R.; Gattinger, P.; Marth, K.; Campana, R.; Mittermann, I.; Blatt, K.; Valent, P.; Selb, R.; Mayer, A.; et al.
Abstract: Background: Administration of the therapeutic anti‐IgE antibody omalizumab to patients induces strong increases in IgE antibody levels. Objective: To investigate the effect of intranasal administration of major birch pollen allergen Bet v 1, omalizumab or placebo on the levels of total and allergen‐specific IgE in patients with birch pollen allergy. Methods: Based on the fact that intranasal allergen application induces rises of systemic allergen‐specific IgE, we performed a double‐blind placebo‐controlled pilot trial in which birch pollen allergic subjects were challenged intranasally with omalizumab, placebo or birch pollen allergen Bet v 1. Total and allergen‐specific IgE, IgG and basophil sensitivity were measured before and 8 weeks after challenge. For control purposes, total, allergen‐specific IgE levels and omalizumab‐IgE complexes as well as specific IgG levels were studied in subjects treated subcutaneously with either omalizumab or placebo. Effects of omalizumab on IgE production by IL‐4/anti‐CD40‐treated PBMCs from allergic patients were studied in vitro. Results: Intranasal challenge with Bet v 1 induced increases in Bet v 1‐specific IgE levels by a median of 59.2%, and this change differed significantly from the other treatment groups ( P = .016). No relevant change in allergen‐specific and total IgE levels was observed in subjects challenged with omalizumab. Addition of omalizumab did not enhance IL‐4/anti‐CD40‐induced IgE production in vitro. Significant rises in total IgE (mean IgE before: 131.83 kU/L to mean IgE after: 505.23 kU/L) and the presence of IgE‐omalizumab complexes were observed after subcutaneous administration of omalizumab. Conclusion: Intranasal administration of allergen induced rises of allergen‐specific IgE levels, whereas intranasal administration of omalizumab did not enhance systemic total or allergen‐specific IgE levels.